Long-term radiological and clinical outcomes after surgical treatment of non-union: a ten-year follow-up study - Jessica C. Böpple; Jonas Berger; Thomas Ferbert; Tim Niklas Bewersdorf; Gerhard Schmidmaier; Sebastian Findeisen (European Journal of Trauma and Emergency Surgery, 2026)
Abstract Purpose Non-unions are a major challenge in trauma surgery. They are known to affect patients’ lives for years after the initial trauma. Nevertheless, most studies only examine the first two years after treatment. The question what the long-term results look like ten years after surgery was posed in light of observations made in everyday clinical practice. To answer this, our study was designed to examine all patients who underwent non-union surgery in our department ten years ago. Methods All patients who underwent surgery between July 2014 and October 2015 were invited to participate in the study. During a one-site appointment, an X-ray image was taken, which was then used to assess consolidation. The patients underwent a physical examination and answered a questionnaire, covering topics such as pain on a visual analogue scale (VAS) and overall quality of life with the short-form 12 (SF-12). Results A total of 54 patients were included in the study. The median follow-up period was 122 months (IQR: 118-124). After 10 years 88.9% patients showed osseus consolidation with a median Lane-Sandhu-Score (LSS) of 4 (IQR: 3–4). The Wilcoxon signed-rank test revealed a significant difference compared to 24 months postoperatively (Z = 4.716, p < 0.001). The difference in the consolidation showed a marginally significant result in the McNemar test with p = 0.063. A total of 51 patients (94.4%) reported being satisfied with the overall treatment. Patients had an average SF-12 mental score of 53.14 ± 10.13 and an SF-12 physical score of 38.93 ± 12.71 after ten years. Compared to the values after 12 months postoperatively, stable values without significant changes were observed. Conclusion The study showed that bone remodeling can still be observed many years after surgical treatment of non-union. Furthermore, it was shown that the clinical results remain stable even after ten years. Clinical trail number DRKS00037034, registered 12.06.2025.